Utilization of Pyrolysis Oil Derived from Landfilled Plastic Waste in a Diesel Engine Generator - Sureeyaphan, Mahidol; Kaewpengkrow, Prangtip Rittichote; Jirawongnuson, Sirichai (My University, 2025)
Plastic waste management in Thailand remains a major challenge, largely due to household waste. Most plastic waste is currently managed through landfilling. Implementing energy recovery methods by pyrolysis is crucial to mitigate this problem. This study investigated the properties and performance of pyrolysis oil from landfilled plastic waste and blended with diesel in different ratios for applying diesel engine generators. The chemical analysis by FTIR technique showed that the pyrolysis oil had a composition close to that of diesel, with suitable C-H and C=C functional groups for combustion. The results revealed that the blended oil’s flash and ignition points increased with the proportion of pyrolysis oil. The pyrolysis oil and diesel blending ratio of 40: 60 obtained the highest flash point at 88.67°C and ignition point at 91.33°C, indicating enhanced combustion efficiency. Meanwhile, the 30:70 blending ratio demonstrated the optimal specific fuel consumption (BSFC) and achieved the highest engine efficiency at 84.94%. Regarding exhaust emissions, all blending ratios resulted in a slight increase in nitrogen oxide (NOx ) emissions, while sulfur dioxide (SO₂) was not detected in any blend. Pyrolysis oil shows promising performance as an alternative fuel, particularly when utilized in optimal blend ratios, as it not only reduces the environmental burden of plastic waste but also contributes to the preservation of fossil fuel resources for future industrial applications.
Keywords: alternative fuel; generator; plastic waste; pyrolysis oil